Experiences of fathers regarding the diagnosis of their child with autism spectrum disorder: A narrative review of the international research - Mc Cann, Edward (My University, 2021)
Aim and objectives The aim of this systematic review was to identify the views and experiences of fathers regarding their child's Autism Spectrum Disorder diagnosis. Background The diagnosis of a child's Autism Spectrum Disorder may be a stressful experience, creating uncertainty for parents. There has been a limited research focus on the views and experiences of fathers in relation to the diagnosis of Autism Spectrum Disorder of their child. Design A systematic literature review of quantitative, qualitative and mixed‐methods research studies. Data Sources Academic Search Complete, CINAHL, MEDLINE and PsycINFO. Methods From August to October 2020, two authors independently performed a systematic data extraction and appraised the studies using a recognised instrument. The PRISMA checklist was used in the review. Results Nine papers met the inclusion criteria. Four themes emerged: (a) gradual recognition of developmental delay, (b) an emotional time, (c) coping and adaptation and (d) ongoing adjustments to the fathering role. Conclusions Nurses and other professionals need to work collaboratively with fathers to improve their experiences and provide supports at the time of Autism Spectrum Disorder diagnosis.
PUBLISHED
Keywords: Autism spectrum disorder; ASD; Fathers; Diagnosis; Nursing; Support; Systematic review; Inclusive Society; Autism Spectrum Disorder; CHILD; FATHERS; INTELLECTUAL DISABILITY; SYSTEMATIC REVIEW